Exile and restoration revisited: essays on the Babylonian and Persian periods in memory of Peter R. Ackroyd - Ackroyd, Peter R.; Knoppers, Gary; Grabbe, Lester L.; Fulton, Deirdre N. (Library of Second Temple studies, 2009)
This volume had its origins in a session presented to the Society of Biblical Literature in Washington in 2006 in order to examine the legacy of Peter Ackroyd to the field of biblical studies. Ackroyd's work stretched over a wide range of topics within Biblical Studies, notably study of prophetic literature and work on exile and restoration. This volume particularly focuses upon his work on the latter. Whilst the present work is founded upon the papers given at the session it also includes several essays solicited subsequently which further serve to draw the contributions together into a fitting tribute to a pioneer in his field. The contributions take account of Ackroyd's approach to the theme of exile and restoration, focusing largely upon the study of Ezra-Nehemiah and Chronciles. As a brief flavour, Bob Becking examines the epigraphic evidence concerning the mixed marriage crisis Ezra-Nehemiah. Joe Blenkinsopp seeks to find the 'Sons of Aaron' before the 5th Century in a fascinating essay focusing which picks up the work of R.H. Kennett over a century ago. Among the other distinguished contributors are John Bergsma, Eric Myers and Jill Middlemass